Síntesis y caracterización de hidrogeles para la cosecha de agua de lluvia y su potencial aplicación en la provincia de Cotopaxi periodo 2021. - Guano Rengifo, Jessica Yessenia (2022)
Global warming is closely linked to climate and the hydrological cycle, bringing with it a decrease in the availability of water resources. For this reason, the objective of the present work was to synthesize and characterize a superabsorbent hydrogel polymer for rainwater harvesting and its potential application in the Cotopaxi Province. Hydrogel polymers were synthesized via free radicals from acrylamide (AAm), at 1%, 2 and 3% N, N-Methyl-en-bis-acrylamide (NMBA), acrylic acid (AAc) at 1% NMBA, and AAm/AAc copolymers in the following proportions: 90/10, 80/20, 70/30, 60/40, 50/50 with 1% NMBA. These hydrogels were evaluated in both distilled water and rainwater to establish the adsorption capacity of each. Using Randomized Complete Block Design (RCBD), swelling curves and FTIR infrared spectroscopy, the swelling percentage and functional structure of the hydrogels could be determined. The results show that there is no great difference in absorption between rainwater and distilled water, with the 1% AAc hydrogel being the best polymer in water uptake with a percentage of 847%. It was also demonstrated that the 1% acrylamide hydrogels and the 90/10 copolymer exceeded 100% water absorption with values of 401% and 349%, respectively. From the statistical analysis it could be verified that the best treatment for water harvesting is the 1% NMBA AAc polymer. In short, all the hydrogels synthesized in this research are superabsorbent hydrogels due to the fact that they exceed 100% water absorption capacity, this is due to the hydrophilic groups by which they are composed. Finally, hydrogels could be an efficient and profitable alternative for farmers in the province of Cotopaxi because they significantly save water, guaranteeing not only the optimization of the water resource but also the quality of the crops.